The Effect of Foreign Direct Investment (FDI) and Labor on the Gross Regional Domestic Product of the Aglicultural Sub-Sector - Ikhsan, Ikhwanul; Indrajaya, Danang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the impact of Foreign Direct Investment (FDI) and labor on the Gross Regional Domestic Product (GRDP) of the agricultural subsector in Indonesia. FDI plays a crucial role in providing resources, technology, and infrastructure necessary to enhance efficiency and productivity in the agricultural sector. On the other hand, labor is a key factor in supporting the operations and management of this sector. This study uses a quantitative approach with purposive sampling to select relevant data according to the research objectives. The analysis technique includes panel data regression testing, hypothesis testing, and the determination coefficient analysis to examine the relationship between the variables studied. The data used is secondary data covering FDI realization, labor, and GRDP of the agricultural subsector from 2019 to 2022. This study is expected to provide a clearer picture of the contribution of FDI and labor to the economic growth of the agricultural subsector and offer useful recommendations for developing more effective agricultural sector policies.